Data visualization and large nursing datasets. - Vincent D; Hastings-Tolsma M; Effken J (Online Journal of Nursing Informatics)
New data visualization software applications allows for the discovery of patterns and trends in large datasets that might not be apparent with traditional data visualization approaches. The purpose of this research was to data mine an existing large dataset utilizing software developed for high-end visual applications to determine whether new patterns or trends that were not evident in prior analyses might be uncovered (Hastings-Tolsma, Vincent, Emeis, & Francisco, 2007). Nurse midwifery data (N=510) had previously been examined to identify factors related to perineal trauma in childbirth; this research reanalyzed the data using Tableau software. Lessons learned about the use of data visualization are presented and challenges and opportunities for using this tool to explore large data sets are discussed.